2014
DOI: 10.1007/s00066-014-0708-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced VEGF-C expression and endothelial cell proliferation in lung cancer

Abstract: BackgroundThe present study was undertaken to investigate whether radiation induces the expression of vascular endothelial growth factor C (VEGF-C) through activation of the PI3K/Akt/mTOR pathway,subsequently affecting endothelial cells.Materials and methodsRadiotherapy-induced tumor micro-lymphatic vessel density (MLVD) was determined in a lung cancer xenograft model established in SCID mice. The protein expression and phosphorylation of members of the PI3K/Akt/mTOR pathway and VEGF-C secretion and mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…It has been reported that gamma rays irradiation induced VEGF-C expression and endothelial cell proliferation in lung cancer. 30 These observations, corroborated with ours, suggest that VEGF-C may be an important therapeutic target for HNSCC patients who relapse after radiotherapy with either P or X.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that gamma rays irradiation induced VEGF-C expression and endothelial cell proliferation in lung cancer. 30 These observations, corroborated with ours, suggest that VEGF-C may be an important therapeutic target for HNSCC patients who relapse after radiotherapy with either P or X.…”
Section: Discussionsupporting
confidence: 82%
“…VEGF is highly expressed in most of human malignant tumors; it promotes endothelial cell proliferation and increases vascular permeability [18]. In the present study, the expression of VEGF was 55.9 %, which indicated that the VEGF expression can be used as an indicator for evaluating prognosis GC.…”
Section: Survival Ratesupporting
confidence: 56%
“…It is possible that these radiation-induced vascular changes may be insufficient to impact tumor control because of vasculogenesis from bone marrow-derived cells that can reconstitute tumor vasculature after radiotherapy (30). It has also been reported that radiation activates VEGF expression, which can promote endothelial cell proliferation (31). Therefore, tumors may be able to redevelop their blood supply after highdose radiotherapy.…”
Section: Discussionmentioning
confidence: 99%